(untitled) (World Bulletin of Management and Law, 2022)
Investment at the level of the Iraqi domestic economy is related to spending from external capital on new projects in the sectors of public utilities and infrastructure, such as projects for paving main and secondary roads, projects for water and sewage extensions, preparing urban plans, construction and housing projects, electricity installations and power generation, as well as social development projects in the fields of education. In addition to projects related to economic activity for the production of goods and services in the productive and service sectors such as industry, agriculture, housing, health, education and tourism. It can also be defined as adding new production energies to the existing productive assets in society by establishing new projects or expanding existing ones, or replacing or renewing projects whose life span has expired, as well as buying issued securities to establish new projects.